Bench marking of grid tied solar roof top photovoltaic system: a case comparison - S. Chopade, Sudhir.; Pankaj Raj. G. N, Lalith; G, Prabakaran (International Journal of Engineering and Technology, 2018)
Indian power sector having the target of 175GW of power from renewable energy, out of that 40 GW from Rooftop solar Photovoltaic system by 2022. The installed capacity of solar photovoltaic until 2017 is about 14.77 GW only. Even though in depth study has been carried out on the performance analysis, there is no bench marking has been arrived for the Indian Roof Top Solar PV system. Hence this paper has made an attempt by calculating the various parameters like performance ratio, plant capacity utilization ratio for the two 20KWp grid connected rooftop power plant in Telangana state. In addition to the above, it needs to do in depth analysis of power quality issues on roof top grid tied system.Â Â